Development and assessment of digital pedagogy competency instrument for teaching and learning: a needs analysis - Md Hashim, Umi Zuraifah; Mohd Puad, Mohd Hazwan; Mohd Ayub, Ahmad Fauzi; Ghazali, Norliza (Human Resource Management Academic Research Society, 2024)
This study aims to identify the difference between digital technology competence using a self-assessment approach compared to a task-based approach among teachers of a secondary school in the Federal Territory of Kuala Lumpur. An interview protocol that was developed and used in this study, consists of six parts where the digital competence of the respondents will be assessed in parts IV and V. In part IV, self-evaluation is done by the respondents using a five-point Likert scale from less proficient to very proficient for Microsoft Word, Microsoft Excel, and Microsoft PowerPoint. In part V, tasks related to Microsoft Word, Microsoft Excel, and Microsoft PowerPoint are given to the same respondent. The data obtained in the formof interviews were transcribed and a comparison between the data of part IV and part V was made. The results found that there is a difference in competency between self-assessment compared to task-based assessment.